2020
DOI: 10.5534/wjmh.190078
|View full text |Cite
|
Sign up to set email alerts
|

Electric Stimulation Hyperthermia Relieves Inflammation via the Suppressor of Cytokine Signaling 3-Toll Like Receptor 4 Pathway in a Prostatitis Rat Model

Abstract: Purpose: Chronic prostatitis (CP), including chronic pelvic pain syndrome (CPPS), is the most commonly encountered manifestation of prostatitis. The aim of this study was to evaluate the effect of electric stimulation hyperthermia treatment (ESHT) on CP/CPPS and to explore the underlying mechanism. Materials and Methods: RWPE-2 cells with lipopolysaccharide-induced inflammation and a prostatitis rat model induced by 17β-estradiol and dihydrotestosterone underwent sham, electric stimulation, or ESHT treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The TLR4/NF-κB signaling pathway has a key role in oxidative stress and the inflammatory response and can suppress the inflammatory response by regulating the TLR4/NF-κB signaling pathway [ 15 ]. It also plays a significant role in the pathogenesis of CNP [ 49 , 50 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TLR4/NF-κB signaling pathway has a key role in oxidative stress and the inflammatory response and can suppress the inflammatory response by regulating the TLR4/NF-κB signaling pathway [ 15 ]. It also plays a significant role in the pathogenesis of CNP [ 49 , 50 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7A, 7B, 7G, 7H ) showed that NLRP3 inflammasome was overexpressed in prostatitis that was down-regulated by ESWT (p<0.05). In addition, as NLRP3 inflammasome components, the immunoreactivity of ASC and caspase-1 proteins were evaluated by immunofluorescence and Western blot as well [ 16 ]. The results ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 EAP mice had increased TLR4 expression and nuclear translocation of NF-κΒ, with an increase in the inflammation score, suggesting that the successfully construction of EAP model. In inflammation, TLR4 is one of the most critical cytokines, 11 while NF-κΒ as the downstream target of TLR4 is able to regulate the release of inflammatory factors (IL-6, IL-8, IL-1β, and TNF-α), thereby gaining an important role in the inflammation, oxidative stress, and immune response. 28 LPS, which is produced by gramnegative bacteria, and other products, such as hyaluronan, heparin, and fibrinogen, have been shown to activate TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are critical to inflammation and immune and pathogen recognition, and among the TLRs, TLR4 has been confirmed to be associated with CP. 10,11 As a TLR member, TLR4 can mediate the activation of nuclear factor-kappa B (NF-κΒ) and cytokine synthesis by the MyD88 pathway, thereby participating in the pathogenesis. 12 Recently, miR-155 deficiency was reported to protect mice from alcohol-induced increase in inflammatory cytokines, and the activated NF-κB was revealed in WT but not in miR-155 knockout alcohol-fed mice.…”
Section: Introductionmentioning
confidence: 99%